COMMUNITY EMPOWERMENT THROUGH THE IMPLEMENTATION OF THE SOCIAL ASSISTANCE PROGRAM FOR UNLIVABLE HOUSES (RUTILAHU) FOR POOR HOUSEHOLDS IN ANTAPANI KULON VILLAGE, BANDUNG CITY - Nanda Nugraha; Abu Huraerah (Journal of Economic Empowerment Strategy (JEES), 2025)
Antapani Kulon Village, Bandung City, is one of the government programs to help poor people have decent housing to live in. The purpose of this study is to describe the program implementation process, supporting and inhibiting factors, ways to overcome obstacles, as well as the theoretical and practical implications of Social Work in social assistance through the implementation of the program (Rutilahu) for poor households so they can restore their social functioning properly. This study uses a qualitative method with a case study approach. The informant selection technique used is purposive sampling. The number of informants in this study is divided into 3 clusters: the DPKP (Regional Disaster Management Agency), the Village, and residents who receive the social assistance program for uninhabitable housing. The data collection techniques in this study used in-depth interviews, observation, and document studies. The results of the study in Antapani Kulon Village produce a description of the process of implementing the social assistance program for uninhabitable housing. No worthy inhabited Which started from planning, preparation, until implementation done. Results The implementation of home improvements was well received by the recipient residents so that the condition of the house is more habitable. However, there are several obstacles such as lack of self-reliance owned by residents, inadequate land location for storing building materials. To solve these problems, it is necessary to improve coordination between the parties involved, and communication must be carried out well. Social work as a professional profession is expected to help in its role with residents receiving assistance in order to help them find alternative solutions to their problems. Social work can also play a role as a social companion for residents receiving assistance and can help them connect with existing resource systems.